Integrated management of seed and seedling rot complex of Soybean - A.N. MUKHOPADHYAY2, RAJEEV PANT1 and (Indian Phytopathology, 2002)
Seed and seedling rot complex of soybean caused predominantly by Rhizoctonia solani Kuhn, Sclerotium rolfsii Sacc., Macrophomina pliaseolina (Tassi) Goid and Fusarium spp. is a major obstacle in increasing soybean production in many countries. It is very difficult to manage these pathogens as their nature of survival is both through the formation of sclerotia chlamydospores and saprophytic phase on soil organic matter. Biological control has emerged as an alternative and promising means for management of such type of diseases.Biocontrol agents like Gliocladium virens and Trichoderma harzianum antagonise pathogens by antibiosis,competition,mycoparasitism or other form of direct exploitation.